Analisa Postur Kerja Menggunakan Metode OWAS dan RULA - Alfin Nur Bintang; Shanty Kusuma Dewi (Jurnal Teknik Industri, 2017)
Material handling activities of sugar in PG Tjoekir storage warehouse is done manually. Continuous material handling activity can cause musculoskeletal disorders to workers. The distribution of questionnaires Nordic Body Map known some complaints experienced by workers in the process of material handling sugar. The OWAS and RULA methods are methods for evaluating and analyzing worker attitudes that can cause musculoskeletal disorders. Some activities in the storage warehouse PG Tjoekir is ranging from lifting, moving and putting sugar. OWAS method calculation results obtained risk level score 3. Risk level risk of RULA method 4. The calculation results show some worker posture causing musculoskeletal risk so that need improvement. Proposed repair work posture is to design two-wheeled hand truck. Hand trucks help reduce the risk of musculoskeletal injuries for workers.